The Influence of Motivation, Working Environment and Career Development Toward Employees’ Loyalty - Nada Fadhila; Endang Sulistiyani (AFEBI Management and Business Review, 2021)
This research aims to determine the effect of motivation, working environment, and career development toward employees’ loyalty at the PT Tawada Healthcare Semarang, which is one of the regional offices of PT Tawada Healthcare. PT Tawada Healthcare Semarang Branch is one of PT Tawada Healthcare office branch, a company engaged in medical devices provider that has been established since 1999. PT Tawada Healthcare has 13 branches throughout Indonesia and also provides medical devices in many hospitals in Indonesia.The data collection method used in this research are questionnaires, literature study, and interview. Sampling method used census which all members of the population are sampled. The methods of data analysis used is Multiple Linear Regression, goodness of fit regression equation used are coefficient of determination, F test and T test. The results of this research shows that motivation, working environment, and career development have positive and significant influence on employees’ loyalty. Working environment has a dominant influence in increasing employee loyalty.Keywords: Career Development, Employees’ Loyalty, Motivation, Working Environment.